OPTIMALISASI HASIL BELAJAR IPA MELALUI MODEL KOOPERATIF NUMBERED HEADS TOGETHER BERBANTUAN WORDWALL PADA MATERI EKOSISTEM DI SEKOLAH DASAR - Maini; Erlia Hanum; Asrul Karim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research addresses the gap between the ideal outcomes expected in the Natural and Social Sciences (IPAS) curriculum and the reality found at UPTD SD Negeri 16 Peusangan, where only half of the fifth-grade students reached the Learning Objective Achievement Criteria (KKTP) on the ecosystem topic, largely due to teacher-centered lecturing and minimal use of interactive media. This study aimed to determine the improvement of student learning outcomes, teacher and student activity, and student responses through the application of the Numbered Head Together (NHT) cooperative learning model assisted by the Wordwall application. The research employed a qualitative-descriptive Classroom Action Research (CAR) design following the Kemmis and Sanjaya model, conducted in two cycles involving 16 fifth-grade students at UPTD SD Negeri 16 Peusangan. Data were collected through tests, observation sheets, and student response questionnaires, then triangulated to ensure validity. The results show that student learning outcomes increased from 62% in Cycle I to 88% in Cycle II, teacher activity rose from 87.5% to 94.5%, student activity rose from 86.5% to 93.5%, and 90% of students gave a very positive response toward the model. It is concluded that the NHT model assisted by Wordwall effectively improves the learning process and outcomes on the ecosystem topic and is recommended as an interactive alternative for elementary science instruction.